Association Between Pulse Pressure and Carotid Intima-Media Thickness Among Low-Income Adults Aged 45 Years and Older: A Population-Based Cross-Sectional Study in Rural China - Liu, Jie; Lin, Qiuxing; Guo, Dandan; Yang, Yuan; Zhang, Xin; Tu, Jun; Ning, Xianjia; Song, Yijun; Wang, Jinghua (Frontiers in Cardiovascular Medicine, 2020)
Worldwide, the stroke burden remains severe, especially for people in low socioeconomic groups. Atherosclerosis is a leading cause of stroke that is attracting increasingly greater attention. Blood pressure, including pulse pressure (PP) and systolic (SBP) and diastolic (DBP) blood pressures, is a traditional risk factor for atherosclerosis; its association with carotid intima-media thickness (CIMT) has also been widely studied. However, published studies have not reported on the relationship between PP and CIMT in low-income adults. Thus, this study investigated the relationship between PP and CIMT in a low-income population, in China. A total of 3789 people, aged ≥45 years and without histories of stroke or cardiovascular disease, were recruited into this study. B-mode ultrasonography was performed to determine CIMTs. Demographic characteristics, physical examination data, previous medical histories, and laboratory test results were collected for each study participant. Multiple linear regression models were used to analyze the association between CIMT and PP. The mean CIMT was 567.1 µm (males, 583.5 µm; females, 555.7 µm). The SBP, DBP, PP, and mean arterial pressure (MAP) values were all positively correlated with CIMT, in the univariate analysis; PP and MAP showed the strongest correlations. In addition, in three multiple linear regression models, PP was shown to be significantly associated with CIMT; each 1-mm Hg increase in PP resulted in a CIMT increase of ≥0.41 µm (all P<0.001). Our results demonstrated that, when compared with SBP, DBP, and MAP, PP may be the best predictor of CIMT. Thus, controlling blood pressure, especially PP levels, is vital to decreasing the prevalence of atherosclerosis, especially in this low socioeconomic status population in China.